Studies on Polygalacturonase from Aspergllus Flavus - Gewali, Mohan B; Maharjan, Jyoti; Thapa, Sambhu; Shrestha, Jaya Krishna (Scientific World, 2010)
Crude polygalacturonase was obtained from Aspergillus flavus cultured in Glucose Free Medium (GFM) by precipitating cell free broth with 66% cold acetone. Effect of different parameters such as temperature, pH incubation time and enzyme concentration on this polygalacturonase preparation was studied. Furthermore, some inhibition studies on this enzyme preparation were conducted. Key words: Aspergillus flavus; Polygalacturonase. DOI: 10.3126/sw.v5i5.2650 Scientific World, Vol. 5, No. 5, July 2007 19-22